Electronic structure of rare-earth erbium-doped platinum diselenide: A density functional theory study - Maleki-Ghaleh, Hossein; Moradpur-Tari, Ehsan; Shakiba, Mohammad; Paczesny, Jan; Hurley, Paul K.; Siadati, M. Hossein; Ansari, Lida; Gity, Farzan (The Journal of physics and chemistry of solids, 2024)
The effect of rare-earth erbium (Er) doping on the electronic structure of platinum diselenide (PtSe2) as a 2D transition metal dichalcogenide was studied using density functional theory (DFT). Our DFT calculations showed that Er dopant in PtSe2 led to the formation of additional states in the valence and conduction bands, and new localized states within the band gap of PtSe2. The orbital-resolved density of states revealed that the 4f orbitals of the dopant Er atom strongly impact the electronic structure of the monolayer PtSe2 and induce spin-polarized localized states. Simultaneously, in addition to a significant increase in the PtSe2 surface energy (52-fold) due to Er doping (from 7.94 × 10−5 to 4.16 × 10−3 eV/Å2), the formation energy of the Er-doped PtSe2 (−328.72 kJ/mol) compared to the pristine PtSe2 (−326.52 kJ/mol) indicates that Er doping has made the PtSe2 system thermodynamically more stable. The results of this study can be used as a guide to design devices for optoelectronic applications such as sensors. [Display omitted] •Er dopant led to the formation of additional states in the valence/conduction bands of PtSe2.•Er dopant created new localized states within the band gap of PtSe2.•Er dopant induced spin-polarized localized states in the band structure of PtSe2.•More than 52-fold enhancement in surface energy of PtSe2 upon Er doping was observed.•Er dopant modulated the electronic structure of PtSe2 by the 4f orbital of Er.